(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: It has been reported in human and animal studies that early exposure to glucocorticoids could retard growth and subsequent development of cardio metabolic diseases. Chronic exposure to glucocorticoids induced oxidative stress. Therefore, the role of oxidative stress in some of the observed metabolic imbalance needs to be elucidated. This study examined the effects of lactational dexamethasone exposure on metabolic imbalance and oxidative stress marker in the liver of male offspring of exposed mother. Twenty lactating dams were divided into 4 groups of 5 animals each. Group 1 was administered 0.02 ml/100gbwt/day normal saline through lactation days 1-21. Group 2, 3, and 4 were administered 100 μg/kgbwt/day dexamethasone for lactation days 1-7, 1-14, and 1-21 respectively. The male offspring were thereafter separated and sacrificed at 12weeks of age for evaluation of lipid profile and oxidative stress marker in the liver. Results from this study indicate that Total Cholesterol (TC), Triglycerides (TAG) and LDL- cholesterol (LDL-C) were significantly (p<0.001) higher in the Dex 1-7, Dex 1-14 and Dex 1-21 groups when compared with the control. HDL-Cholesterol (HDL-C) was significantly (p<0.001) reduced in the Dex 1-7, Dex 1-14 and Dex 1-21 groups relative to the control. Basal Fasting Blood Sugar (FBS) was also significantly (p<0.001) higher in the Dex 1-14 and Dex 1-21 groups when compared with the control. Liver malondialdehyde was significantly (p<0.001) higher in the Dex1-14 and Dex1-21 group compared to the control. However, liver catalase and SOD activity were all significantly (p<0.001) lower in Dex 1-7, Dex 1-14 and Dex 1-21 groups relative to control. Liver protein was significantly (p<0.001) lower in the Dex1-14 and Dex1-21 treatment groups when compared with the control. Findings from this study suggest that there is possible increase in metabolic imbalance in the offspring of mother exposed to dexamethasone during lactation and these effects may be secondary to increase oxidative stress in the liver.